Prinsip Ekonomi Syariah dalam Pengelolaan Sumber Daya Manusia: Studi pada Usaha Sabar Abadi Pondok Pesantren Syubbanul Wathon - Taufik, Akhmad; Rifai, Fuad Yanuar Ahmad; Aini, Qurotul (Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2025)
This study aims to analyze the implementation of Islamic economic principles in human resource management at Sabar Abadi Welding and Construction Business of Syubbanul Wathon Islamic Boarding School. This research employs a qualitative approach using a field study design. Data analysis was conducted interactively following the Miles and Huberman model, which includes data reduction, data display, and conclusion drawing. The findings reveal that human resource management in this pesantren business reflects Islamic values through work as worship, commitment to excellence, cooperation, honesty, and responsibility. These values have shaped a productive, ethical, and fair work culture. The application of Islamic economic principles in santri work practices not only improves efficiency and work quality but also fosters spiritual awareness and social responsibility. This study is expected to serve as a model for developing Islamic human resource management in other pesantren-based business units to strengthen economic independence based on Islamic values.